Síndrome do cão tremedor - Hünning, Paula Stieven; Rigon, Grazziane Maciel; Aguiar, Juliana; Stedile, Rafael; Colomé, Lucas Marques (Acta Scientiae Veterinariae, 2018)
Background : : : : The Shaker Dog Syndrome manifests itself as generalized tremors that usually affect the head and body of the patient. The tremors increase with movement and decrease at rest, and it may cease during sleep. The disorder develops mostly in 1-year to 5-year-old animals weighing below 15 kg. The diagnosis is based on the exclusion of other possible causes of tremors and a positive response to treatment with corticosteroids. The treatment consists of immunosuppressant doses of corticosteroids and it can be associated to decreasing diazepam doses during 8 to 12 weeks. Literature data are very rare and cannot be found in Brazil. Consequently, this study aimed at describing a Shaker Dog Syndrome case that is responsive to corticosteroids. Case: A 2-year-old mongrel female dog, weighting 7.5 kg, was referred to the Hospital de Clínicas Veterinárias da Universidade Federal do Rio Grande do Sul, presenting generalized tremors for 5 days, which would cease during sleep. In the neurological examination, the cranial nerve exam and the test for postural reactions were considered normal. The hematological and biochemical profile did not show alterations. The cervical spine radiography did not display bone alterations. A density of 1.016 was observed at the physical examination of the cerebrospinal fluid. The chemical examination revealed a glucose level of 100 mg/dL, negative bilirubin, negative ketones, absence of occult blood, pH 8.0, presence of protein traces, normal urobilinogen, negative reactive protein C (PCR), normal creatine kinase (CK) and aspartate aminotransferase (AST). The result of Pandy’s test was negative. Oral treatment with prednisone at a dose of 1.5 mg.kg-1 BID and diazepam at a dose of 0.5 mg.kg-1 BID was instituted, this latter during 4 days. The corticoid dose was maintained until total disappearance of the tremors, which occurred within 24 days. Afterwards, a gradual reduction of 50% of the dose was made every 7 days, during 4 weeks. Discussion: During anamnesis, tremors induced by trauma and medication were ruled out. Myelin abnormalities were also improbable, as they cause congenital tremors and do not quickly respond to corticosteroids. A colorless aspect and absence of occult blood and bilirubin was observed in the LCR analysis. The absence of turbidity and the presence of protein traces in this sample demonstrate normality (38.7 mg/dL ± 15.49). Chemical and physical exams did not demonstrate alterations – pH 8.0 (8.30 ± 0.34) and a density of 1.016 (1007 ± 1.83), respectively. The glucose concentration in the cerebrospinal fluid was not reduced. The results obtained from Pandy’s and reactive protein C tests were negative. The analysis of AST and CK enzymes was normal. Since the values obtained from enzymatic and protein evaluations of the cerebrospinal fluid were normal, they suggest an absence of infectious and degenerative processes. The immunosuppressant prednisone dose recommended by literature is variable; thus, the smallest corticosteroid dose indicated was selected, which is 1.5 mg.kg-1 BID. An association with diazepam was made to reduce tremors. Usually, clinical improvement can occur within a few days, but the remission of clinical signs can take weeks. In the present case, the reduction of tremors occurred on the fourth day, with the complete disappearance in 24 days, without recurrence within a clinical follow-up period of 2 years.